Oolong Tea-Derived Manganese Nanoparticles as an Alternative Oral Negative Contrast Agent for MRCP Imaging - Fatimah, Fatimah; Susilaningsih, Neni; Sukmaningtyas, Hermina; Subagio, Agus (Scripta Medica, 2026)
Background/Aim: Conventional natural manganese contrast agent for magnetic resonance cholangiopancreatography (MRCP) have produced suboptimal visualisation of the gastric, duodenum and biliary system. While various studies have explored manganese-based media, limited research has focused on manganese nanoparticles (Mn-NPs). This study investigated oolong tea-derived Mn-NPs as a potential alternative oral contrast agent for MRCP imaging, aiming to enhance image clarity while minimising neurotoxic effects in healthy volunteers.Methods: A true experimental approach with a pre-test and post-test control group setup was employed, involving thirty healthy volunteers divided into three groups: (K1) Mn-NPs derived from oolong tea, (K2) manganese extracted from oolong tea and (K3) standard manganese chloride. Signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR) and blood levels of IL-1β and TNF-α were assessed pre- and post-contrast administration for efficacy and neurotoxicity.Results: The extracted Mn-NPs of oolong tea decreased signal strength in the stomach (3.40 %) and the duodenum (1.60 %), while increasing signal blockage in the gallbladder (0.80 %), cystic duct (4.40 %), common hepatic duct (13.80 %), intrahepatic duct (4.10 %), common bile duct (4.10 %) and pancreatic duct (3.10 %). These results outperformed those of standard contrast agent and manganese sourced from oolong tea. IL-1β (3.24 pg/mL) and TNF-α (6.9 pg/mL) levels showed no neurotoxic effects. Mn-NPs from oolong tea showed superior imaging performance. This is due to their long residence time and stronger magnetic properties. The anti-inflammatory compounds in oolong tea likely contributed to the stable cytokine levels observed, indicating a good safety profile. In addition, integration with the FIESTA MRI suite further enhances image contrast.Conclusion: Mn-NPs prepared from oolong tea can be used instead of traditional contrast agent in MRCP examinations. They provide better image quality and do not harm the brain.
Keywords: Oolong tea; Nanoparticles; Manganese; Cholangiopancreatography, magnetic resonance